Activity phenomena in the baryonic universe as a result of interaction between baryonic objects and the carrier of darkenergy - Harutyunian, H. A.
Non-stable phenomena are under consideration for rather long time. Mostly two issues seem to be very essential in connection with non-stability, namely, their role in the evolution of cosmic objects and the sources providing energy for non-stability manifestations. We argue here that the energy exchange with the dark energy carrier may be the main mechanism of energy providing. Backed by the contemporary ideas about the dark energy, we accept that this new-found energy homogeneously fills all space at all scales and interacts with cosmic objects belonging to all hierarchical levels. We argue that baryons mass is changeable quantity depending on the environmental physical conditions and therefore it is a subject of evolution as the objects of other hierarchical classes. Moreover, we argue in favour of new paradigm to be used for the further development of cosmology and cosmogony, which is not based on the a priory hypothesis by Kant and Laplace.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture